Interest premium and economic growth: the case of CEE - Dániel Baksa; István Kónya (Hungarian Academy of Sciences, Institute of Economics, 2017)
This paper views the growth and convergence process of the four Visegrad economies - the Czech Republic, Hungary, Poland and Slovakia - through the lens of the open economy, stochastic neoclassical growth model. We use a unified framework to understand both the long-run convergence path and fluctuations around it. Our empirical exercise highlights both the role of initial conditions such as indebtedness and capital intensity, and random shocks in the growth process. In particular, we explore the importance of the external interest rate premium, and its role in driving investment and the trade balance.
Keywords: E13; O11; O41; O47; 330; stochastic growth; technology shocks; interest premium; small open economy; Bayesian estimation; Wirtschaftswachstum; Zins; Technologie; Schock; Wirtschaftliche Konvergenz; Kleine offene Volkswirtschaft; Neoklassisches Wachstumsmodell; Visegrad-Staaten